Examining Determinant Factors on Online Shopping Behavior upon Buying Furniture - Aryo Prayudhana; Adrian Adrian; Arum Mardikawanti; Yonatan A. Hendro; Natasya N. Nugroho (Indonesian Business Review, 2022)
The research is dedicated to examine factors that affect online shopping behavior of consumers upon buying furniture. These factors might be an important issue regarding e-commerce and marketing in the online furniture retail market. However, knowledge about online consumer behavior is still very limited because it is a fairly complex phenomenon in social life that can involve too many factors, especially in buying furniture online. One of the aims of this research is to uncover factors that have not been studied in previous studies, especially in the furniture industry. To acquire in-depth information, 10 informants were interviewed. Coding method was used to analyze the factors revealed in the transcript. The research identified that attitude (Financial Risk, Product Risk, Convenience Risk, Service and Infrastructure Variation), domain specific innovativeness, subjective norm (Family and Reference Group), and perceived behavior control (Playfulness and Informativeness) affect consumer purchase intention and thus affect their online shopping behavior in buying furniture online. The framework presented in the conclusion section will help further research on which factors influence the most.